Konvensjoner om faste kulturminner:: Norges forpliktelser og utfordringer til fagmiljøet - Hanssen-Bauer, Françoise (Hikuin, 2006)
Konvensjoner om faste kulturminner: Norges forpliktelser og utfordringer til fagmiljøet By Françoise Hanssen-Bauer Since 1961, Norway has ratified seven international conventions on the cultural heritage and its protection. The author presents two of these conventions, the so-called Granada and Malta conventions that Norway ratified in 1996 and 1995 respectively. She focuses her discussion on a few articles in these conventions, and claims that these express a general approach to preservation which implies several challenges and requirements to the concerned professions and communities. She summarizes three emerging dilemmas: - Preserving vs. use and access; - Expert control over decision making vs. participation of the public; - Developing national professional traditions vs. European collaboration and coordination